Do as I say, not as I do: Distracted driving behavior of teens and their parents. (December 2015) - Raymond Bingham, C.; Zakrajsek, Jennifer S.; Almani, Farideh; Shope, Jean T.; Sayer, Tina B.
Abstract: Introduction: Driver distraction is an important contributor to crash risk. Teenage driver distraction can be influenced by the attitudes and behaviors of parents. This study examined teens' and their parents' engagement in distracting behavior while driving. Method: Survey data were collected from a national sample of 403 parent-teen dyads using random-digit dialing telephone interviews. Results: Results demonstrated few parent or teen sex differences in distracting behavior engagement while driving, or in their perceptions of each others' behavior. Parents and teens' frequencies of distracting behavior engagement were positively correlated. Parents' and teens' perceptions of each others' distracting behavior engagement while driving exceeded their own selfreports. Finally, the likelihood that teens reported engaging in distracting behavior while driving was more strongly associated with their perceptions of their parents' distracting behavior than by parents' self reports of their own behavior. Conclusions: These results suggest that parents' examples of driving behavior are an important influence on teen driving behavior, but potentially more important are teens' perceptions of their parents' behaviors. Highlights: Parents and teens both overestimate each other's involvement in distracting behaviors while driving. Parents' and teens' levels of involvement in distracting behaviors are correlated. Teens participation in distracting behavior is more strongly influenced by their perceptions of their parents distracting behavior than by what parents themselves report.